Collective memories and social roles: the case of the Paris terrorist attacks of 13 November 2015 - Orianne, Jean-François; Heiden, Serge; Klein-Peschanski, Carine; Eustache, Francis; Peschanski, Denis (Frontiers in Sociology, 2024)
The present study was based on empirical data collected during the first phase (2016) of Study 1000, part of the 13-November Program: a corpus of 934 individual interviews conducted 6-11 months after the events. To process this empirical material, the authors used integrated TXM software, which provides several classic textometry tools. They mainly used the lexical specificity analysis tool, which statistically measures the irregularity of the word distribution according to the parts of the corpus. They also analyzed the concordances of certain very specific lexical forms. Analysis revealed the important influence of social roles on the construction of memories and narratives of this event. Application of textometry tools highlighted lexical fields specific to the different social roles played by the interviewees in this social drama, and showed that it was through these specific vocabularies that they remembered and recounted this extraordinary story. Social roles therefore influence the formation of memories both individual and collective, by modulating the way in which individuals select what to remember and what to forget. The article opens up several interesting avenues for future analyses, mainly a longitudinal perspective (including phases 2 and 3 of Study 1000) for the study of flashbulb memories and the gender issue to fine-tune the analysis of social roles.